Analysis of Internal Audit Planning in Improving the Effectiveness of Organizational Performance at the Btm Sinar Mentari Tuban Cooperative - Hariyanti Hariyanti; Yudi Supiyanto; Niniek Widiarochmawati; Dede mariyani; Bashirotul Mufaqqih Amrullah (Pelopor Publikasi Akademika, 2024)
This study aims to describe the implementation of an internal audit in the BTM Sinar Mentari Tuban Cooperative and to describe internal audit planning in increasing the effectiveness of the performance of the BTM Sinar Mentari Tuban Rice Cooperative organization. Data collection techniques are carried out using questionnaires, observations, and interviews. Data analysis techniques are measurements with a Likert scale and descriptive statistics. Based on data analysis conducted on internal audits in increasing the effectiveness of organizational performance at the BTM Sinar Mentari Tuban cooperative, it can be seen that The results of research on the effectiveness of the role of internal audit at the Sinar Mentari BTM Cooperative show effective results. This can be seen from the calculation results showing 92.80%. The results of calculating the effectiveness of the company's performance show 92.46%; this means that the company's performance will be effective if there is an internal audit role in the company.